Intracellular Trafficking of Cationic Carbon Dots in Cancer Cell Lines MCF-7 and HeLa-Time Lapse Microscopy, Concentration-Dependent Uptake, Viability, DNA Damage, and Cell Cycle Profile - Havrdová, Markéta; Urbančič, Iztok; Tománková, Kateřina Bartoň; Malina, Lukáš; Poláková, Kateřina; Štrancar, Janez; Bourlinos, Athanasios B (International journal of molecular sciences, 2022)
Fluorescent carbon dots (CDs) are potential tools for the labeling of cells with many advantages such as photostability, multicolor emission, small size, rapid uptake, biocompatibility, and easy preparation. Affinity towards organelles can be influenced by the surface properties of CDs which affect the interaction with the cell and cytoplasmic distribution. Organelle targeting by carbon dots is promising for anticancer treatment; thus, intracellular trafficking and cytotoxicity of cationic CDs was investigated. Based on our previous study, we used quaternized carbon dots (QCDs) for treatment and monitoring the behavior of two human cancer cell MCF-7 and HeLa lines. We found similarities between human cancer cells and mouse fibroblasts in the case of QCDs uptake. Time lapse microscopy of QCDs-labeled MCF-7 cells showed that cells are dying during the first two hours, faster at lower doses than at higher ones. QCDs at a concentration of 100 µg/mL entered into the nucleus before cellular death; however, at a dose of 200 µg/mL, blebbing of the cellular membrane occurred, with a subsequent penetration of QCDs into the nuclear area. In the case of HeLa cells, the dose-depended effect did not happen; however, the labeled cells were also dying in mitosis and genotoxicity occurred nearly at all doses. Moreover, contrasted intracellular compartments, probably mitochondria, were obvious after 24 h incubation with 100 µg/mL of QCDs. The levels of reactive oxygen species (ROS) slightly increased after 24 h, depending on the concentration, thus the genotoxicity was likely evoked by the nanomaterial. A decrease in viability did not reach IC 50 as the DNA damage was probably partly repaired in the prolonged G0/G1 phase of the cell cycle. Thus, the defects in the G2/M phase may have allowed a damaged cell to enter mitosis and undergo apoptosis. The anticancer effect in both cell lines was manifested mainly through genotoxicity.
Keywords: MCF-7 Cells; Cell Line; biologický transport; DNA Damage; HeLa; genotoxicity; uhlík; Quantum Dots; reaktivní formy kyslíku; cationic carbon dots; Biological Transport; poškození DNA; Optical Imaging; HeLa Cells; Mice; Cell Proliferation; MCF-7; kvantové tečky; nucleus; cancer cells; fluorescence microspectroscopy; MFC-7 buňky; cytotoxicity; kontrolní body fáze G2 buněčného cyklu; Carbon; Neoplasms; Reactive Oxygen Species; optické zobrazování; zvířata; časosběrné zobrazování; Humans; nádory; G2 Phase Cell Cycle Checkpoints; viabilita buněk; Cell Survival; Fibroblasts; myši; proliferace buněk; buněčné linie; Time-Lapse Imaging; HeLa buňky; lidé; fibroblasty; Animals